Perspektywa bio- i neurolingwistyczna jako nowa determinanta w badaniach nad językiem - Krysiak, Adrian Piotr (Investigationes Linguisticae, 2010)
This article presents a neurobiological approach to linguistic research. The author describes its main neurological methods and discusses the latest findings. Some advanced achievements, including the origins of language, the mirror neurons issue and some controversies concerning FOXP2, a gene involved in the development of language skills, are also discussed. Language influence on human sociosexual behaviour has been established. The author also indicates the possibility of a new bioelectronical approach.